Performance Management in the Public Administration : Seven Success Factors - Schnell, Sabina; Mihes, Dimitrie; Sobjak, Anita; van Acker, Wouter (World Bank, Washington, DC, 2021)
This EFI Insight note distills the key principles of effective performance management in the public administration from literature and international good practice. First, it presents the objectives and different approaches and tools for performance management, and then it details seven success factors that should be considered when designing and reforming public sector performance management systems: (1) start performance management from the top; (2) align organizational and individual goals (‘clear line of sight’); (3) tailor performance assessment to institutional and job characteristics, and adequately differentiate between levels of performance; (4) improve manager judgment and diversify the sources of information for performance appraisals to ensure objectivity and fairness in assessment; (5) motivate staff through both intrinsic and extrinsic incentives; (6) enable staff through adequate opportunities for growth and development; and (7) embed performance management in organizational culture and practice.